UPAYA MEMBANGUN KEUTUHAN KELUARGA DI PESANTREN HIDAYATULLAH BALIKPAPAN MENURUT TINJAUAN MAQASHID SYARIAH - Paryadi Paryadi; Sofia Hardani (CV. ADIBA AISHA AMIRA, 2022)
The family divorce rate in Indonesia is high and concerning because it is increasing every year. So many families fall apart and children become victims of broken homes. Despite various government efforts to build family integrity. The Hidayatullah Islamic Boarding School in Balikpapan has made various efforts to condition the integrity of the family. The results showed that the Hidayatullah Islamic Boarding School Balikpapan from the preparation of official houses, the establishment of educational institutions, parents' schools, parenting, social and health institutions, problem solving assemblies, sports facilities, financial institutions and zakat. This is relevant to maqashid shari'ah, namely the protection of ushul khamsah (religion, soul, mind, lineage and property) especially in the daruriyyah aspect.